Exploring the Research Progress of Traditional Chinese Medicine Therapy on Prediabetes based on “Preventive Treatment of Disease” - Zhang, Shumin; Wang, Defen; Zhao, Tian (Journal of Contemporary Medical Practice, 2025)
In Chinese medicine, the idea of “preventive treatment of diseases” emphasizes “preventive treatment of diseases before they occur, preventive treatment of changes in existing diseases, and preventive treatment of recurrence after recovering from a disease”, as the law of prevention and treatment, reversing the initial stage of the disease. pre-diabetes is the excessive stage of diabetes development, and the use of Traditional Chinese medicine therapy in pre-diabetes is an effective means of preventing and controlling the development of diabetes. This article introduces the clinical progress of different forms of Chinese medicine therapy, such as Chinese herbal decoction, Chinese proprietary medicine, Chinese herbal diet therapy, Traditional Chinese medicine herbal infusion, and Traditional Chinese medicine therapy, from the etiology of pre-diabetes, in order to provide more theoretical bases and references for the prevention and treatment of pre-diabetes by Chinese medicine therapy.